2019
DOI: 10.1108/et-10-2018-0210
|View full text |Cite
|
Sign up to set email alerts
|

Becoming a professional

Abstract: PurposeResearch into the experience of BSc Psychology students and graduates in the graduate transition was carried out to enquire if ontology is central to educational transformation; if professional work experience is important in the process of becoming; and how graduates experience the transition from student to professional. Design / methodologyIn this qualitative longitudinal in-depth interview investigation four one-year work placement students were interviewed twice and five graduates were interviewed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…Various studies have addressed the role of changing position from a beginner to an expert in the formation of professional competencies. For example, Reddy and Shaw (10) stated that the transition from being a beginner to an elite is an important component of the formation of professional competencies. Other studies conducted in other fields have shown that transition from the beginner level to expertise is a step or essential component of the formation of professional competencies (11)(12)(13).…”
Section: Discussionmentioning
confidence: 99%
“…Various studies have addressed the role of changing position from a beginner to an expert in the formation of professional competencies. For example, Reddy and Shaw (10) stated that the transition from being a beginner to an elite is an important component of the formation of professional competencies. Other studies conducted in other fields have shown that transition from the beginner level to expertise is a step or essential component of the formation of professional competencies (11)(12)(13).…”
Section: Discussionmentioning
confidence: 99%
“…Co-creation stimulates creativity and innovation skills necessary to deal with the issues of the current society (Bovill, 2011;Rill & Hä mä lä inen, 2018). Furthermore, HE alumni experience the transition from being a student to being a professional as difficult (Reddy & Shaw, 2019). Young professionals struggle with different responsibilities and expectations, such as "being pro-active", and using their expertise in professional contexts (Monteiro et al, 2020).…”
Section: Co-creation As Effective Learning Environment For Studentsmentioning
confidence: 99%
“…In relation to becoming an IT professional, Clark et al (2011) proposed that the transition to IT work is best understood by taking fields, habitus, capital, and the interactions between them into consideration. And in relation to becoming a professional in the field of psychology, Reddy and Shaw (2019) pinpointed the importance of searching for oneself, the integration of knowing and acting, and judgment grounded in acting; at the same time, they suggested that teaching alone is insufficient to facilitate the transition.…”
mentioning
confidence: 99%